2020
DOI: 10.21203/rs.3.rs-82494/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Psychological Effect of COVID-19 and Lockdown on the Population: Evidence from Italy

Abstract: The COVID-19 pandemic and the lockdown measures adopted to prevent the spread of the disease had a huge impact on a personal, social, and economic level for the world population. In Europe, Italy was one of the frontrunner countries dealing with an emergency that significantly affected people’s lives. Previous research on the psychological impact of the pandemic revealed an increase in anxiety, depression, and feelings of distress; however, these studies were conducted on non-representative samples of the popu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The estimated self-reported rates of depression (18.7%), anxiety (18.7%), and stress (21.5%) symptoms among our sample (surveyed during the period of June–October 2020) were lower than those reported in the Italian general population [ 35 , 36 , 37 ] and in Italian general healthcare workers [ 35 , 38 , 39 ] using the same measurement during the period of March–May 2020. However, our rates are slightly higher than the 14.4% rate of depressive symptoms registered by an Italian population study in June 2020 [ 40 ] and notably higher than those reported by pre-pandemic Italian population-based studies, showing prevalence rates of 5.4 and 7% for depressive symptoms and anxiety, respectively [ 41 ]. In our study, about 5% of PHPs suffered from burnout, while other Italian studies using the same assessment tool found that just less than one-third of health professionals had burnout during the first three months of the COVID-19 outbreak [ 35 , 38 ].…”
Section: Discussioncontrasting
confidence: 80%
“…The estimated self-reported rates of depression (18.7%), anxiety (18.7%), and stress (21.5%) symptoms among our sample (surveyed during the period of June–October 2020) were lower than those reported in the Italian general population [ 35 , 36 , 37 ] and in Italian general healthcare workers [ 35 , 38 , 39 ] using the same measurement during the period of March–May 2020. However, our rates are slightly higher than the 14.4% rate of depressive symptoms registered by an Italian population study in June 2020 [ 40 ] and notably higher than those reported by pre-pandemic Italian population-based studies, showing prevalence rates of 5.4 and 7% for depressive symptoms and anxiety, respectively [ 41 ]. In our study, about 5% of PHPs suffered from burnout, while other Italian studies using the same assessment tool found that just less than one-third of health professionals had burnout during the first three months of the COVID-19 outbreak [ 35 , 38 ].…”
Section: Discussioncontrasting
confidence: 80%
“…While these measures were effective in controlling viral transmission, they are expected to have a negative impact on the psychosocial health of the community [ 3 , 4 , 5 ]. Psychological distress was reported between 12 and 52 percent in older adults during this pandemic [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We do this on the basis of a complex empirical methodology that combines the advantages of an extensive survey on a random sample representative of the Italian population with a series of psychometric measures and tests on the ability of citizens to comprehend the epidemiological phenomenon and to correctly distinguish true from fake news. This methodology is based both on consolidated and robust techniques of inferential statistics and innovative methods scienti cally validated in the psychometric component (see Delmastro and Zamariola 2020) and in the testing of perceptions (see Alesina et al 2018) and the evaluation of news reliability (see Allcot and Gentzkow, 2017, Allcot et al 2019, and Delmastro and Leonardi, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we controlled for the effect of the lockdown measures introducing a dummy variable that is equal to 1 whenever the individual kept on going to the workplace during the lockdown period and is 0 in the opposite situation of people staying at home. To evaluate mood and feelings of the Italian population, a psychometric approach was adopted (see Delmastro and Zamariola, 2020). Due to the special nature of the period which prevents to conduct experimental studies meeting participants face-to-face, a psychometric self-reporting methodology was chosen.…”
Section: Measures Of Covariant Dimensionsmentioning
confidence: 99%